Pengaruh Iklan Internet, Harga Dan Promosi Terhadap Keputusan Pembelian Pada Aplikasi Mobile Commerce - Wimpertiwi, Dotty; Sunarto, Abdul Rosid; Nurhaliza, Bella; Suputra, Made Esa Kameswara (Journal of Business, Management, and Social Studies, 2022)
The purpose of this study was to determine the effect of internet advertising, promotions and prices on consumer purchasing decisions on mobile commerce applications. This study employed a quantitative method, sample selection using a non-probability sampling technique in the form of purposive sampling. The sample used is the general public in Jakarta, the primary data is obtained from questionnaires distributed online. Based on the results of data processing and statistical tests, the researchers succeeded in proving that there was indeed a significant effect of advertising, prices, and promotions on purchasing decisions made by consumers in m-ommerce applications.